Sunday

April 20, 2014

April 20, 2014

Posted by **ang** on Saturday, March 16, 2013 at 9:24pm.

- math -
**Jeff**, Saturday, March 16, 2013 at 9:58pmCombine the like terms

(6a^4b - 6a^4b) + (ab^3 + 3ab^3)

= 0a^4b + 4ab^3

= 4ab^3

**Related Questions**

MATH - EVALUATE 6a + 4b - 3c WHEN a=4, b=7, AND c= -2

math - 16a - 5b - (-6a - 15b) - (-4b)

algebra - (6a^3bc^5)(-3a^4b^2c^3) simplify

maths - How do i factorise 1)6a^2b^3+12a^4b 2)2m^2+9m-5

Math - Simplify 2a^2 b^3 (4a^2 + 3ab -ab) A.) 8a^4 b^5 + 3a^3 b^5 - 2a^3 b^4 B...

math - 3a^2b + 6a^2b 9a^4b^2

CP Algebra - Simplifying fractions. I can get from this: 4b^2-5b-6 __________ 8b...

Am I doing Algerba right? - 6a for a = 3 and a = -4 So is it A. 6a = 6*3 = 18? B...

algebra - evaluate a-13 when a =33 evaluate 3x+2y-2z when x =5 y=2 z=1 evaluate ...

Trig - 3. In the figure below, the perimeter of the parallelogram ABCD is (6a + ...